Pharmacological Evaluation and Preliminary Pharmacokinetics Studies of a New Diclofenac Prodrug without Gastric Ulceration Effect - dos Santos, Jean Leandro [UNESP]; Moreira, Vanessa; Campos, Michel Leandro [UNESP]; Chelucci, Rafael Consolin [UNESP]; Barbieri, Karina Pereira [UNESP]; Maggio de Castro Souto, Pollyana Cristina; Matsubara, Marcio Hideki; Teixeira, Catarina; Bosquesi, Priscila Longhin [UNESP]; Peccinini, Rosangela Goncalves [UNESP]; Chin, Chung Man [UNESP] (Mdpi Ag, 2012)
Long-term nonsteroidal anti-inflammatory drugs (NSAIDs) therapy has been associated with several adverse effects such as gastric ulceration and cardiovascular events. Among the molecular modifications strategies, the prodrug approach is a useful tool to discover new safe NSAIDs. The 1-(2,6-dichlorophenyl)indolin-2-one is a diclofenac prodrug which demonstrated relevant anti-inflammatory properties without gastro ulceration effect. In addition, the prodrug decreases PGE(2) levels, COX-2 expression and cellular influx into peritoneal cavity induced by carrageenan treatment. Preliminary pharmacokinetic studies have shown in vivo bioconversion of prodrug to diclofenac. This prodrug is a new nonulcerogenic NSAID useful to treat inflammatory events by long-term therapy.
Keywords: NSAIDs; anti-inflammatory; diclofenac; prodrugs; molecular modification; lactam; COX-inhibitor; bioconversion; chronic inflammation